Overexpression of pregnane X and glucocorticoid receptors and the regulation of cytochrome P450 in human epileptic brain endothelial cells - Ghosh, Chaitali; Hossain, Mohammed; Solanki, Jesal; Najm, Imad M.; Marchi, Nicola; Janigro, Damir (Epilepsia (Copenhagen), 2017)
Summary Objective Recent evidence suggests a metabolic contribution of cytochrome P450 enzymes (CYPs) to the drug‐resistant phenotype in human epilepsy. However, the upstream molecular regulators of CYP in the epileptic brain remain understudied. We therefore investigated the expression and function of pregnane xenobiotic (PXR) and glucocorticoid (GR) nuclear receptors in endothelial cells established from post‐epilepsy surgery brain samples. Methods PXR/GR localization was evaluated by immunohistochemistry in specimens from subjects who underwent temporal lobe resections to relieve drug‐resistant seizures. We used primary cultures of endothelial cells obtained from epileptic brain tissues (EPI‐ECs; n = 8), commercially available human brain microvascular endothelial cells (HBMECs; n = 8), and human hepatocytes (n = 3). PXR/GR messenger RNA (mRNA) levels in brain ECs was initially determined by complementary DNA (cDNA) microarrays. The expression of PXR/GR proteins was quantified by Western blot. PXR and GR silencing was performed in EPI‐ECs (n = 4), and the impact on downstream CYP expression was determined. Results PXR/GR expression was detected by immunofluorescence in ECs and neurons in the human temporal lobe samples analyzed. Elevated mRNA and protein levels of PXR and GR were found in EPI‐ECs versus control HBMECs. Hepatocytes, used as a positive control, displayed the highest levels of PXR/GR expression. We confirmed expression of PXR/GR in cytoplasmic‐nuclear subcellular fractions, with a significant increase of PXR/GR in EPI‐ECs versus controls. CYP3A4, CYP2C9, and CYP2E1 were overexpressed in EPI‐ECs versus control, whereas CYP2D6 and CYP2C19 were downregulated or absent in EPI‐ECs. GR silencing in EPI‐ECs led to decreased CYP3A4, CYP2C9, and PXR expression. PXR silencing in EPI‐ECs resulted in the specific downregulation of CYP3A4 expression. Significance Our results indicate increased PXR and GR in primary ECs derived from human epileptic brains. PXR or GR may be responsible for a local drug brain metabolism sustained by abnormal CYP regulation.